Chemical and Biological Aspects of Montanine-Type Alkaloids Isolated from Plants of the Amaryllidaceae Family - Koutová, Darja; Maafi, Negar; Havelek, Radim; Opletal, Lubomír; Blunden, Gerald; Řezáčová, Martina; Cahlíková, Lucie (Molecules (Basel, Switzerland), 2020)
Plants of the Amaryllidaceae family are promising therapeutic tools for human diseases and have been used as alternative medicines. The specific secondary metabolites of this plant family, called Amaryllidaceae alkaloids (AA), have attracted considerable attention due to their interesting pharmacological activities. One of them, galantamine, is already used in the therapy of Alzheimer's disease as a long acting, selective, reversible inhibitor of acetylcholinesterase. One group of AA is the montanine-type, such as montanine, pancracine and others, which share a 5,11-methanomorphanthridine core. So far, only 14 montanine-type alkaloids have been isolated. Compared with other structural-types of AA, montanine-type alkaloids are predominantly present in plants in low concentrations, but some of them display promising biological properties, especially in vitro cytotoxic activity against different cancerous cell lines. The present review aims to summarize comprehensively the research that has been published on the Amaryllidaceae alkaloids of montanine-type.
Keywords: Cholinesterase Inhibitors; Antineoplastic Agents, Phytogenic; Cell Line, Tumor; rostlinné extrakty; Nootropic Agents; antiprotozoální látky; nootropní látky; biological activity; pancracine; Amaryllidaceae Alkaloids; Secondary Metabolism; montanine-type; derivatives; Inhibitory Concentration 50; alkaloids; Heterocyclic Compounds, 4 or More Rings; heterocyklické sloučeniny tetra- a více cyklické; Plant Extracts; lidé; alkaloidy amarylkovitých; Amaryllidaceae; isochinoliny; Humans; Galantamine; galantamin; Isoquinolines; montanine; sekundární metabolismus; inhibiční koncentrace 50; Antiprotozoal Agents; nádorové buněčné linie; Phenanthridines; fytogenní protinádorové látky; cholinesterasové inhibitory; fenantridiny